DOMAIN DISPUTES: PROBLEM ASPECTS - Diduk, Alla; Lytvyn, Stepan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: the purpose of this article is to clarify the main problems of litigation of domain disputes and suggest ways to overcome them. The methodological basis of the study are general scientific and special methods of cognition. The use of these methods made it possible to describe the problems of litigation of domain disputes. Results: the study found that neither domestic law nor domestic justice is ready to deal with cases related to domain disputes. Because in practice they face the problem of clarifying judicial jurisdiction and the impossibility of applying the rules of international law. The plaintiff faces the problem of identifying the defendant, there are difficulties in proving and the need to file a statement of claim. And the plaintiff, most often, can only be the owner of a registered trademark (mark for services). Discussion: it is possible to overcome the existing problems of litigation of domain disputes by improving the procedure of domain name registration, which will prevent violation of the rights of owners of means of individualization of participants in civil circulation, goods and services, and in case of violation of these rights.